Analisis dan Perancangan Situs Web Alumni Sistem Informasi dan Teknik Informatika IBI Kwik Kian Gie - Humdiana Humdiana (Jurnal Informatika dan Bisnis, 2014)
Information system develops rapidly that enable alumnus to get in touch each other. This research isintended to analyze and design website connecting IBII alumnus mutually and to do tracing study.Thisalumnus website uses PHP programming language and assisted by mySQL database utilized normalizedtable.Collecting data are done by observation and interviewing. Research is using analytic and individualmethod. Design is using Unified Modelling Language (UML) process. The result of this research is analumnus website that is enable to connect alumnus mutually and to do alumnus tracing study.Alumnuswebsite is able to make alumnus connecting each other and sharing mutually, also for IBII to do alumnustracing study easily.